Percepção ambiental sobre a APA de Campinas: subsídios para educação ambiental - Marostica, Luandra Danielle [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
In the face of the visible growth of environmental issues, especially in cities, it is of great concern to seek and propose solutions to minimize negative impacts and even extinguish them when possible. Conservation units are in place to protect and preserve what remains of forests and fauna and flora biodiversity, as well as to provide maintenance and protection of water sources. In the case of Environmental Protection Areas, such conservation extends to the sustainable use of natural resources and adequate land use. The chosen area for this study is an Environmental Protection Area (Campinas/SP APA) inserted in a context of rapid urban growth and sprawl, however with rural areas still prevailing. Protecting remaining forests, preserving headwaters and preventing uncontrolled growth, among others, are priorities in these areas, so that they do not lose even more of their natural environment and so future generations may also enjoy such quality. This study aims to contribute to future environmental education in the area, bringing subsidies through semi-structured questionnaires to groups of people linked to the APA (local residents, residents of condominiums and enclosed allotments, visitors, public organs and non-governmental organizations). These subsidies come in the form of data on the perception, knowledge, opinions and socioeconomic information of the respondents. It is important to get to know those who live and visit the APA so as to apply an education about the environment properly and efficiently, taking into account the different relationships present in each group towards the APA. The results of this research are presented in tables and graphs for easier viewing of the issues approched on environmental perception and the profile of those surveyed in the APA. The main results found show that the majority of respondents are aware of what are protected areas and the study site (APA), as well as the importance of preserving these...

Diante do visível crescimento dos problemas ambientais, principalmente nas cidades, é importante a preocupação em procurar e propor soluções para minimizar os impactos negativos e até mesmo extingui-los. As Unidades de Conservação atuam de forma a proteger e conservar o que ainda resta de matas e da biodiversidade de fauna e flora, além da preocupação com a manutenção e proteção dos mananciais. No caso das Áreas de Proteção Ambiental, essa conservação se estende ao uso sustentável dos recursos naturais e do uso e ocupação ordenada do solo. A região de estudo é uma Área de Proteção Ambiental (APA de Campinas/SP) inserida em um contexto de acelerado crescimento urbano, mas que ainda prevalecem as áreas rurais. Proteger os remanescentes de matas, preservar as nascentes, impedir o crescimento descontrolado, entre outros aspectos, são prioridades nessas áreas, para que não se perca ainda mais o ambiente natural e para que as próximas gerações também possam usufruir com qualidade. O presente estudo visa contribuir com futuros programas de Educação Ambiental na área, trazendo subsídios resultantes da aplicação de questionários semiestruturados para grupos de pessoas ligadas a APA (moradores de bairros, moradores de condomínios e loteamentos fechados, visitantes, órgãos públicos e organizações não governamentais). Estes subsídios vêm em forma de dados sobre a percepção, conhecimento, opiniões e informações socioeconômicas dos entrevistados. É importante conhecer quem vive e visita a APA para que se possa aplicar uma educação sobre o meio ambiente de forma adequada e eficiente, levando em consideração as diferenças de relacionamento de cada grupo com a APA. Os resultados dessa pesquisa estão demonstrados em forma de tabelas e gráficos, facilitando a visualização das questões abordadas sobre a percepção ambiental e o perfil dos entrevistados da APA. Como principais resultados...
Keywords: Educação ambiental; Unidades de conservação; Terras públicas; Áreas de conservação de recursos naturais; Impacto ambiental; Desenvolvimento sustentável; Solo - Uso; Crescimento urbano; Proteção ambiental; Campinas (SP)